The Effectiveness of The Hello, Me! Program to Increase Teengaers’ Self-Awareness - Ulya, Laila Listiana; Stanislaus, Sugiyarta; Amawidyati, Sukma Galuh Adi; Mahanani, Fatma Kusuma; Arinata, Firdian Setiya (Universitas Negeri Semarang, 2021)
During the Covid-19 pandemic, unemployment increased to 9.77 million. Youth competition in the world of work will be more challenging if they do not have soft and hard skills. Teenagers who grow up in an environment with complex social problems such as Tikungbaru, where poverty, crime, and juvenile delinquency rates are high, actually need it. Teenagers need self-awareness to select the right career. The purpose of the research was to determine the